Associação entre achados abreugráficos de cardiomegalia e manifestações clínicas Association between X-ray evidence of cardiomegalia and clinical manifestations - Afonso Dinis Costa- Passos; João Cláudio Flores-Cardoso; Antônio Ruffino-Netto (Universidade de São Paulo, 1987)
Com o objetivo de estudar possível associação entre achados abreugráficos de cardiomegalia e sinais e/ou sintomas clínicos registrados na primeira consulta, foram analisados os prontuários de 700 pacientes atendidos no Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto, SP - Brasil, durante o período de 25/9/1967 a 25/9/1969. Foram tomados 700 controles pareados com os casos segundo sexo e grupo etário. Encontrou-se associação entre achados de cardiomegalia e o registro de queixas referentes a dor precordial, tosse e/ou expectoração, edema e hemoptise, bem como entre cardiomegalia e idade. Sugere-se, quando o objetivo específico for diagnosticar alterações cardíacas, limitação do uso da abreugrafia apenas a grupos pré-selecionados segundo idade e presença de pelo menos uma das queixas assinaladas. A possible association between megalocardia and clinical signs and/or symptoms registered in the records of a university hospital (Clinical Hospital of the Ribeirão Preto Medical School, Brazil) was studied. In order to carry out the research a case control study was developed. Those patients who showed enlargement of the cardiac area diagnosed by roentigenphotography when moment they were seen in the Hospital for the first time (700 cases) were included. For each case a control corresponding to a patient who had also had his first consultation at the same Hospital, and whose roentgenphotography showed no cardiac enlargement, was selected. Cases and controls were seen during the period from September 25th, 1967 to September 25th, 1969. They were matched according to sex and age. The presence or absence of the following complaints was sought in the cases' and controls' records: precordial ache, cough and/or expectoration, edema, pain in the right upper part of the abdomen, hemoptysis, palpitation and dyspneia. An association between megalorcardia and the following signs and/or symptoms was established; precordial ache, cough and/or expectoration, edema and hemoptysis, as well as the patient's age. Due to these findings it is suggested that the use of roentgenphotography as a diagnostic method for cardiac abnormalities should be restricted to population groups that are previously selected according to age and the presence of at least one of the five above mentioned complaints.